Retrospective Analysis of Hydatid Cyst Patients and Incidence of CNS Involvement in Southern Rajasthan - Gautam, Sachidanand; Kumar, Baibhav; Gautam, Bhawana; Gupta, Gaurav; Jain, Banesh (Nepal Journal of Neuroscience, 2025)
Introduction: Echinococcosis also known as hydatid disease is an endemic zoonotic disease with an estimate of 2,00,000 new cases per year worldwide. Its primary definitive host is dog and man being an accidental intermediate host. The most common organ affected is liver, brain, and spine. Surgery is the mainstay of treatment and medical management is reserved for selected cases. Our Objective was to retrospectively  evaluate  the prevalence of craniospinal hydatid cyst disease in southern Rajasthan.Materials and method: A retrospective analysis of all cases of craniospinal hydatid disease managed at our department was done from 2013 to 2021 and data was analysed.  Results: A total number of eight cases were reported with an incidence of 1.8% of all craniospinal space-occupying lesions during the study period with a male to female ratio of 3:1, mean age of presentation 18.5 years, four out of eight patients were in paediatrics age group. All cases were managed surgically with preoperative rupture in one case and recurrence in two cases. Albendazole was given to cases only with rupture or recurrence.Conclusions: Craniospinal hydatid disease should be suspected in all non-enhancing cystic brain lesions especially in endemic regions. In all patients, surgical excision should be done preferably with medical management reserved for inaccessible lesions, unfit patients, rupture and recurrent cases only. The study concludes that primary surgery with gross total excision with no or minimal spillage of cyst content intraoperatively has good results with recurrence rate of only 12.5%.